Utility of the Surgical Apgar Score for Patients Who Undergo Surgery for Spinal Metastasis. Issue 8 (October 2017) - Lau, Darryl; Yee, Timothy J.; La Marca, Frank; Patel, Rakesh; Park, Paul
Abstract : Study Design: Retrospective review of patients who underwent surgery for spinal metastasis between 2005 and 2011. Objective: To assess the utility of the surgical Apgar score (SAS) in patients who underwent surgery for spinal metastasis. Summary of Background Data: Surgery for spinal metastasis can be associated with relatively high morbidity and mortality. Consequently, identifying patients at risk for major postoperative complications is important. Several studies have validated SAS for predicting 30-day complication risk. Methods: SASs were calculated and patients stratified into 5 groups: scores 0–2, 3–4, 5–6, 7–8, 9–10 points. Multivariate logistic regression assessed whether SAS was an independent predictor of major complication 30 days after surgery. Multivariate analysis of covariance assessed whether SAS was independently associated with length of stay. Results: Ninety-seven patients with a variety of metastatic tumors were analyzed. There was no obvious trend in complication rates, or significant association between SAS and complication rate ( P =0.413). Complication rates were 25.0% for SASs 0–2, 33.3% for 3–4, 18.4% for 5–6, 10.0% for 7–8, and 33.3% for 9–10 points. On multivariate analysis, SAS was not independently associated with complications; age above 65 years (odds ratio 4.19; 95% confidence interval, 1.31–52.27; P =0.028) and preoperative Karnofsky Performance Score of 10–40 (odds ratio 9.13; 95% confidence interval, 1.42–58.63; P =0.020) were associated with higher odds of complication. SASs 0–2 were an independent predictor of longer hospital stay ( P =0.004). Conclusions: Our findings suggest that SAS is not a significant predictor of major perioperative complications after spinal metastasis surgery; preoperative functional status and age are stronger predictors. The need continues for a preoperative scoring system to reliably predict risk for perioperative complications after spinal metastasis surgery.